1971
DOI: 10.1002/aic.690170403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gibbs adsorption on marangoni instability

Abstract: SCOPEIn the transfer of mass from one fluid phase to another, solute concentration gradients or temperature gradients may produce surface tension gradients, resulting in cellular convection at the interface. In liquid-liquid extraction systems the convection may become so intense that it causes the break-up of the interface, resulting in "spontaneous emulsification." Often referred to as Marangoni instability, convection driven by surface tension gradients also occurs frequently in gas-liquid mass transfer sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…Our treatment here will be for instabilities driven by energy transport between the two phases. Recent work by Palmer and Berg (1972) and Brian (1971) has shown that in the case of mass transfer accumulation of mass in the Gibbs layer may have profound stabilizing effects on surface tension driven instabilities. In cases for which the instability arises primarily as the effect of buoyancy or shear, however, the two transport mechanisms are analogous.…”
Section: Homsymentioning
confidence: 98%
“…Our treatment here will be for instabilities driven by energy transport between the two phases. Recent work by Palmer and Berg (1972) and Brian (1971) has shown that in the case of mass transfer accumulation of mass in the Gibbs layer may have profound stabilizing effects on surface tension driven instabilities. In cases for which the instability arises primarily as the effect of buoyancy or shear, however, the two transport mechanisms are analogous.…”
Section: Homsymentioning
confidence: 98%
“…Since the main objective of this paper is to investigate the effect of the non-diffusing boundaries on the critical parameters and the mass transfer enhancement behaviour of RBM convection, Gibbs adsorption effects have been neglected in the present analysis (Brian, 1971;Brian and Ross, 1972;Palmer and Berg, 1972;Sun and Fahmy, 2006).…”
Section: Governing Equations For the Perturbed Statesmentioning
confidence: 99%
“…Such motions sometimes called interfacial turbulence or Marangoni convection (Brian 1971;Bragard et al 1994) are, if adequately controlled, quite effective to promote heat and/or mass transfer across the surfaces. For developing advanced heat/mass transfer technology utilizing surfactant solutions, dynamic as well as static properties of adsorbed surfactant films covering the solution surfaces should be well known.…”
Section: Introductionmentioning
confidence: 99%